Sextortion: Caracterização dogmática e delimitação da imputação criminal em Portugal = Sextortion : dogmatic characterization and limitation of criminal imputation in Portuga - Ramalho, Joaquim José dos Santos (Revista Eletrônica de Direito Penal e Política Criminal, 2023)
Sextortion, like cybercrime in general, is a crime that has been experiencing an increase in prevalence, with the law showing difficulties in its classification and differentiation from other crimes. Thus, this article aims to conduct a reflexive approach on the imputation of criminal responsibility in Portugal, seeking to standardize its classification and avoid doctrinal divergences. In imputation, based on a stricto sensu conception, the crime of sextortion is subsumed in the authorized possession of the victim's images and, through the threat of sharing them in cyberspace, seeking to obtain financial advantage, new intimate content and face-to-face encounters.